Financial Work Incentives for Disability Benefit Recipients: Lessons from a Randomised Field Experiment - Monika Bütler; Eva Deuchert; Michael Lechner; Stefan Staubli; Petra Thiemann (Institute for the Study of Labor (IZA), 2014)
Disability insurance (DI) beneficiaries lose part of their benefits if their earnings exceed certain thresholds (cash-cliffs). This implicit taxation is considered the prime reason for low DI outflow. We analyse a conditional cash program that incentivises work related reductions of disability benefits in Switzerland. 4,000 randomly selected DI recipients receive an offer to claim up to CHF 72,000 (USD 71,000) if they expand work hours and reduce benefits. Initial reactions to the program announcement, measured by call-back rates, are modest; individuals at cash-cliffs react more frequently. By the end of the field phase, the take-up rate amounts to only 0.5%.
Keywords: H55; J14; C93; D04; 330; disability insurance; field experiment; financial incentive; return-to-work